Manufacturing Process Application for Lecture Chair - Nidhomuz Zaman, Akhmad; Sari, Santika (UNIPA PRESS, 2021)
A Learning environment is a place where the learning process takes place. In the implementation of the learning process, most student activities are carried out in a sitting position. Therefore the conditions and seating arrangements, the shape of the chairs, the various equipment and facilities that support the teaching and learning process must be a concern. An uncomfortable sitting position can affect the quality of learning. Also, uncomfortable lecture chairs will affect the user's concentration in learning so that this condition will accelerate the onset of fatigue. The application of the production process that we carried out for the manufacture of our redesigned lecture chairs (flexible chair) has been produced with a total time of 370 minutes with parts, namely, the mainframe, headrests, leg rests, back frame, and supporting materials with a total of 5 operators. We hope that this article can help other fellow students to produce an item and make an analysis of the production process.